Microsoft Office Access 2003: A Beginner's Guide - Sheldon Robert (McGaw-Hill Osbrne Media, 2003)
No matter your information management needs, this easy-to-follow resource will show you how to collect and process data, customize data entry, share it through secure pathways, and create your own processing rules. Designed for easy comprehension, this helpful guide gives you step-by-step explanations supported by relevant examples and exercises.